2022
DOI: 10.30574/wjarr.2022.16.3.1384
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Hemato-biochemical urinary profile of diabetic patients received in consultation at anastasis health center in Nongo (Conakry), Republic of Guinea

Abstract: Introduction: Diabetes is a group of metabolic diseases characterized by chronic hyperglycemia resulting from a defect in insulin secretion or insulin action or both associated abnormalities. Objective: Our study aims to contribute in improving of health care of diabetic patients in the Municipality of Ratoma, Conakry, and Republic of Guinea. Methods: This study is a prospective and descriptive cross-sectional study lasting of 4 months, from February 16 to June 16, 2021. Results: The study involved 300 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Our research at the Diabetology, Endocrinology, and Metabolic Diseases Department of Alpha Oumar Diallo Regional Hospital in Kindia (Republic of Guinea) showed that out of 220 patients, 150 (68%) exhibited unbalanced glucose levels ranging from 1.30 to 2 g/l, with an additional 22 patients (10%) showing very unbalanced levels (>2 g/l), while 48 patients (22%) maintained balanced levels (0.80 -1.26 g/l) (Figure 1). These figures compare to a 2021 study by Camara C., et al ( 2022) [3] at the ANASTASIS Health Center in Nongo, Conakry, which found very unbalanced glucose levels in 11.33% of patients, unbalanced levels in 9.33%, and only 0.33% with balanced glucose levels among 300 examined. Although our findings align with their results for unbalanced and very unbalanced glucose levels, there is a marked disparity in the proportion of patients with balanced levels-22% in our study versus only 0.33% in theirs.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Our research at the Diabetology, Endocrinology, and Metabolic Diseases Department of Alpha Oumar Diallo Regional Hospital in Kindia (Republic of Guinea) showed that out of 220 patients, 150 (68%) exhibited unbalanced glucose levels ranging from 1.30 to 2 g/l, with an additional 22 patients (10%) showing very unbalanced levels (>2 g/l), while 48 patients (22%) maintained balanced levels (0.80 -1.26 g/l) (Figure 1). These figures compare to a 2021 study by Camara C., et al ( 2022) [3] at the ANASTASIS Health Center in Nongo, Conakry, which found very unbalanced glucose levels in 11.33% of patients, unbalanced levels in 9.33%, and only 0.33% with balanced glucose levels among 300 examined. Although our findings align with their results for unbalanced and very unbalanced glucose levels, there is a marked disparity in the proportion of patients with balanced levels-22% in our study versus only 0.33% in theirs.…”
Section: Discussionsupporting
confidence: 58%
“…Type 2 diabetes mellitus is the most common type of diabetes, accounting for over 90% of all cases, and is the fifth leading cause of death among people aged 50 to 74 [1]. This type of diabetes is part of a group of metabolic diseases characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both [3]. This leads to a number of severe complications, thereby reducing the quality of life and functional abilities of patients [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations